A novel guided surgery system with a sleeveless open frame structure: a retrospective clinical study on 38 partially edentulous patients with 1 year of follow-up - Jaafar Mouhyi; Maurice Albert Salama; Francesco Guido Mangano; Carlo Mangano; Bidzina Margiani; Oleg Admakin (BMC, 2019)
Abstract Background This retrospective clinical study aims to present results of experience with a novel guided surgery system with a sleeveless, open-frame structure, in which the surgical handpiece (not the drills used for preparation) is guided. Methods This study was based on an evaluation of the records of partially edentulous patients who had been treated with a sleeveless open-frame guided surgery system (TWIN-Guide®, 2Ingis, Brussels, Belgium), between January 2015 and December 2017. Inclusion criteria were patients with good systemic/oral health and a minimum follow-up of 1 year. Exclusion criteria were patients who had been treated without a guide, or with a guide with sleeves, patients with systemic/oral diseases and who did not have a follow-up of 1 year. The main outcomes were surgical (fit and stability of the surgical guide, duration of the intervention, implant stability, and any intra-operative or immediate post-operative complication), biologic, and prosthetic. Results Thirty-eight patients (24 males, 14 females; mean age 56.5 ± 14.0 years) were included in the study. These patients had been treated with 110 implants inserted by means of 40 sleeveless, open-frame guides. With regard to fit and stability, 34 guides were excellent, 4 acceptable, and 2 inadequate for use. The mean duration of the intervention was 23.7 (± 6.7) minutes. Immediately after placement, 2 fixtures were not stable and had to be removed. Two patients experienced pain/swelling after surgery. The 108 surviving implants were restored with 36 single crowns and 32 fixed partial prostheses (24 two-unit and 8 three-unit bridges); these restorations survived until the 1-year follow-up, with a low incidence of biologic and prosthetic complications. Conclusions Within the limits of this study, this novel guided surgery system with sleeveless, open frame-structure guides seems to be clinically reliable; further studies on a larger sample of patients are needed to confirm these outcomes.